Acid Base Module with SETS Approach to Train Students’ Critical Thinking Skill - Anis Mualifah; Rusmini Rusmini (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
Acid Base Module with SETS Approach to Train Student Critical Thinking Skills. This study aimed to develop an acid-base module with SETS approach to train students' critical thinking skills. The study used Borg Gall Research and Development (RD) method until the limited trial stage. The limited trial was carried out on 12 students of class XI at SMAN 1 Dongko Trenggalek. Then, the developed module was tested for its feasibility based on 3 aspects, namely validity, practicality and effectiveness. The module's validity data was obtained from the results of the assessment from two chemistry lecturers and one chemistry teacher. The module obtained validity percentages of 84.1% for content, 84.17% for presentation and 83.33% for language with a valid category. The module's practicality was obtained from the student response questionnaire results, where the practicality percentage of the module was 98.81% with a very practical category. The module's effectiveness was known from the students’ critical thinking skills improvement based on the pretest and posttest scores and obtained n-gain score average of 0.79 with high category. It is supported by the Wilcoxon test results, which obtained Asymp.Sig 0.05 (0.002 0.05), so that Ha is accepted. So, it can be concluded that the acid-base module with the SETS approach can train students' critical thinking skills